Clinical profile of measles in children with special reference to infants. (January 2019) - Sindhu, TG; Geeta, MG; Krishnakumar, P; Sabitha, S; Ajina, KK
This study was conducted to analyse the clinical characteristics of measles in infants and to compare them with those in older children. Clinical and sociodemographic details of all hospitalised children with suspected measles were recorded and confirmed cases were analysed further. Twenty-four infants and 34 children aged >1 year were included. Most infants were boys and 15 (62.5%) of them were aged <9 months. Early onset of rash (within three days of fever in 62.5% of cases) occurred in infants. The complications of measles in infants included bronchopneumonia (n = 17, 71%), acute diarrhoea (n = 8, 33%), meningitis (n = 1, 4%) and staphylococcal sepsis (n = 2, 8%). The number of infants with complications was significantly high (88% and 65%; P = 0.05). Measles in infants can have atypical presentations, a greater risk for complications and may occur before they are due to receive the conventional first dose of measles vaccine.